2020
DOI: 10.1021/acssuschemeng.0c01734
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Fibers from Lignin–Cellulose Precursors: Effect of Carbonization Conditions

Abstract: Carbon fibers (CFs) are gaining increasing importance in lightweight composites, but their high price and reliance on fossil-based raw materials stress the need for renewable and cost-efficient alternatives. Kraft lignin and cellulose are renewable macromolecules available in high quantities, making them interesting candidates for CF production. Dry-jet wet spun precursor fibers (PFs) from a 70/30 w/w blend of softwood kraft lignin (SKL) and fully bleached softwood kraft pulp (KP) were converted into CFs under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
79
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(91 citation statements)
references
References 39 publications
7
79
1
4
Order By: Relevance
“…The increase in the ratio of I D /I G is directly in contrast to carbon bres made from PAN where this ratio is seen to decline with the increasing carbonisation temperature [56][57][58] . However, these ndings are in complete agreement with reported Raman results on the carbon bres obtained from lignin 4,20 . Moreover, it is reported that the higher molecular weight of lignin enhances the graphitic structure and mechanical performance 59 .…”
Section: Electrical Conductivity Of Electro-spun Asl-esl Carbonised Lsupporting
confidence: 92%
See 3 more Smart Citations
“…The increase in the ratio of I D /I G is directly in contrast to carbon bres made from PAN where this ratio is seen to decline with the increasing carbonisation temperature [56][57][58] . However, these ndings are in complete agreement with reported Raman results on the carbon bres obtained from lignin 4,20 . Moreover, it is reported that the higher molecular weight of lignin enhances the graphitic structure and mechanical performance 59 .…”
Section: Electrical Conductivity Of Electro-spun Asl-esl Carbonised Lsupporting
confidence: 92%
“…This band is a result of second order resonance from the D-band and it is normally referred to as 2D band. This 2D band is a characteristic feature of increased stacking in the layered graphitic sheets 4,54 .…”
Section: Electrical Conductivity Of Electro-spun Asl-esl Carbonised Lmentioning
confidence: 94%
See 2 more Smart Citations
“…Thus, less expensive, and preferably bio‐based raw materials for carbon fibers are sought for. Recent research has shown great promise in carbon fibers produced from a combination of lignin and cellulose 7,8 . The advantage of using lignin and cellulose is that they are both bio‐based and abundant materials, thus enabling a less expensive carbon fiber 9 .…”
Section: Introductionmentioning
confidence: 99%